PENGARUH BEBAN KERJA DAN INSENTIF TERHADAP TURNOVER INTENTION KARYAWAN PT. ALFA DINAMIS INDO TEKNIK - Hotner Tampubolon; Jonny Siagian; Fajrianwar Erizal (Universitas Kristen Indonesia, 2026)
Fajrianwar Erizal, The Effect of Workload and Incentives on Employee Turnover Intention at PT. Alfa Dinamis Indo Teknik This research is a quantitative study that aims to understand the impact of Work Environment and Employee Engagement on Employee Turnover Intention at PT. Alfa Dinamis Indo Teknik. The population of this study consists of 34 employees of the company. Data collection technique using a needle (cuesioner). The method of data analysis that is used is the berganda regression analysis method. The research found a significant effect on the turnover intention of PT. Alfa Dinamis Indo Teknik employees with a p-value of 0.001, which is less than 0.05. The significant effect on the turnover intention of PT. Alfa Dinamis Indo Teknik employees was found in the Insentif variable (X2) with a significance level of 0.000 < 0.05. Beban kerja dan insentif secara simultan berpengaruh signifikan terhadap turnover intention, sebagai hasil uji simultan nilai signifikan sebesar 0,001 < 0,005. According to the adjusted R-squared value of 91.9%, job insecurity and work ban had an effect on turnover intention, while the other variable not examined in this study had an effect size of 8.1%. This study's findings suggest that companies should make more of an effort to keep their employees engaged in the company and specifically at PT. Alfa Dinamis Indo Teknik if they want to boost employee engagement and retention. KE INDONESIA Keywords : Work load, Insentif and Employee Performance